ADMINISTRATION OF ISOLATED PROBIOTICS FROM THE DIGESTIVE TRACT PRAWNS (Macrobranchium rossenbergii De Man) AND TIGER SHRIMP (Penaeus monodon) TO IMPROVE THE IMMUNITY OF TILAPIA (Oreochromis niloticus) - Mohd. Ramadhani; Mery Sukmiwati; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aims to determine the effect of probiotics isolated from the digestive tract of prawns (Macrobranchium rosenbergii De MAN) and tiger shrimp (Penaeus monodon) to improve the immunity of tilapia (Oreochromis niloticus) against the disease. The method used is the experimental method. The best probiotic given is genera Bacillus UG4 and combined genus Bacillus (UG1 + UG2 + UG3 + UG4 + UG5) derived from the digestive tract prawns. As for the isolates from the gastrointestinal tract tiger shrimp used UWH9 best isolates and isolates combined (UWH1 + UWH2+ UWH8+UWH9 +UWH10). The best treatment in this study were treated with the probiotic isolates UWH9 capable of withstanding the impairment of erythrocytes, hemoglobin, hematocrit and leukocytes after infection with pathogenic bacteria. Keywords : Probiotics, Haematology, Tilapia, Immunity